Seedling variants in allspice (Pimenta dioica (L.) Merr.) - REMA, P A MATHEW, B KRISHNAMOORTHY, J (Journal of Spices and Aromatic Crops, 1999)
Allspice (Pimento dioica (L.) Merr.), also known as Jmnaican pepper, is indigenous to West Indies. The mature but unripe perries are dried and used as a spice. Alls.pice was introduced into India by the British during the 18th century. In India, it is mainly cultivated in few estates of Ashamboo hills (Kanyakumari District, Tamil Nadu), and also in a few gardens in Bengal, Bihar, Orissa, Karnataka, Kerala and Tamil Nadu. Allspice is commonly propagated through seeds.